Commodity Price Shocks and Imperfectly Credible Macroeconomic Policies in Commodity-Exporting Small Open Economies - Medina Guzman, Juan Pablo (IMF Working Papers; Working Paper, 2014)
In this paper, we analyze how lack of credibility and transparency of monetary and fiscal policies undermines the effectiveness of macroeconomic policies to isolate the economy from commodity price fluctuations. We develop a general equilibrium model for a commodity-exporting economy where macro policies are conducted through rules. We show that the responses of output, aggregate demand, and inflation to an increase in commodity price are magnified when these rules are imperfectly credible and lack transparency. If policies are imperfectly credible, then transparency helps private agents to learn the systematic behavior of the autorities, reducing the effects of commodity prices shocks. Coherent with the model, we show cross-country evidence that monetary policy transparency and fiscal credibility reduce the incidence of export price volatility on output volatility. Also, our results indicate that having an explicit fiscal rule and an inflation targeting regime contribute to isolate the economy from terms of trade fluctuations.